2010
DOI: 10.1155/2010/715872
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis on the Structural and Magnetic Properties of Bulk and Nanocrystalline Cu-Fe-O

Abstract: Nanocrystalline and bulk samples of “Fe”-doped CuO were prepared by coprecipitation and ceramic methods. Structural and compositional analyses were performed using X-ray diffraction, SEM, and EDAX. Traces of secondary phases such as CuFe2O4, Fe3O4, andα-Fe2O3having peaks very close to that of the host CuO were identified from the Rietveld profile analysis and the SAED pattern of bulk and nanocrystalline Cu0.98Fe0.02O samples. Vibrating Sample Magnetometer (VSM) measurements show hysteresis at 300 K for all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Such lattice distortion explains the material stability due to the formation of CuFe 2 O 4 on the surface. 65 …”
Section: Discussionmentioning
confidence: 99%
“…Such lattice distortion explains the material stability due to the formation of CuFe 2 O 4 on the surface. 65 …”
Section: Discussionmentioning
confidence: 99%
“…The average grain size for PVA is found to be 114nm to 234nm. Well defined nanocrystalline morphology of CuO is shown in Fig.4(b).The particles are rod like [35] in shape having an average grain size from 52nm to 84nm. The grains are found to be well interconnected with each other which indicate that they have enough binding energy to combine with neighbour grains or molecules.…”
Section: Scanning Electron Microscopy and Edx Analysismentioning
confidence: 97%
“…In the same sense, by using the microwave combustion method, Mohamed et al [23] synthesized Fe-doped CuO nanostructures with x ¼ 0, 0.05, 0.1, 0.15, and 0.20. They show that Fe ions were successfully introduced into the lattice substituting the Cu ions without affecting the crystal structure of the CuO host [9]. According the above mentioned experimental results, the formation of spurious phase in Fe-doping CuO samples seems to be dependent of the growth method.…”
Section: Resultsmentioning
confidence: 83%
“…Besides, the strong magneto-phonon interaction and the quasi-one-dimensional nature of T-dependence of magnetic susceptibility have also been the subject of many reports found in the literature [3][4][5][6][7]. Recent studies showed that the simultaneous observation of the magnetic and electronic transport (semiconductor) properties in CuO samples doped with magnetic ions have attracted attention of the scientific community due to their high potential of application as spintronic devices [8,9]. Meneses et al [10] show that the disorder in the spatial distribution of magnetic ions and the change in the cell parameters can play an important role in the magnetic properties of the TM-doped CuO samples.…”
Section: Introductionmentioning
confidence: 99%